The Effect of Welfare, Mutation and Promotion on Employee Work Performance at the Pioneer Detacle of the Korsabhara Baharkam Headquarters of the Republic of Indonesia Police - M. Adjie Perdana; Yuni Pratikno; Jamal Hanaffy (Dinasti International Journal of Digital Business Management, 2026)
Employee performance is an important indicator in assessing the success of the implementation of organizational tasks and functions, especially in the Pioneer Detachment of Korsabhara Baharkam Headquarters of the Republic of Indonesia Police. This study aims to analyze the influence of Welfare, Transfers, and Promotions on Employee Performance, both partially and simultaneously. This study uses a quantitative approach with a survey method, where data is collected through distributing questionnaires to 105 respondents of the Pioneer Detachment of Korsabhara Baharkam Headquarters of the Indonesian National Police. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that partially Welfare has a positive and significant effect on Employee Performance with a t-value of 3.266 and a significance of 0.001, Transfers have a negative and significant effect on Employee Performance with a t-value of -1.867 and a significance of 0.005, and Promotions have a positive and significant effect on Employee Performance with a t-value of 2.033 and a significance of 0.045. Simultaneously, Welfare, Transfer, and Promotion have a significant effect on Employee Work Performance with an F value of 6.635 and a significance of <0.001. The coefficient of determination (R Square) of 0.465 indicates that Welfare, Transfer, and Promotion are able to explain 46.5% of the Employee Work Performance variable, while the remaining 53.5% is influenced by other factors outside the research model. The results of this study confirm that improving employee welfare, implementing appropriate transfer policies, and an objective and transparent promotion system are strategic factors in improving employee work performance within the Pioneer Detachment of Korsabhara Baharkam Mabes Polri